2000
DOI: 10.1046/j.1525-1594.2000.06621.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Outcome After Mechanical Ventricular Support Using Thoratec, Novacor, and HeartMate for Bridging to Heart Transplantation

Abstract: Between September 1989 and June 1999, 228 patients were supported with a ventricular assist device as a bridge to heart transplantation. In this study, the results of implantation were evaluated in patients supported with one type of device, including 85 supported with a Thoratec, 61 with a Novacor, and 37 with a HeartMate. The mean support time was 49, 148, and 124 days, respectively. Successful transplantation and weaning rates were 64. 7% with Thoratec, 59.0% with Novacor, and 62.0% with HeartMate. Cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…The survival rate associated with fulminant myocarditis has been increasing with advances in various systems of MCS. 3 Methods of VAB such as percutaneous cardiopulmonary support (PCPS) or extracorporeal membrane oxygenation (ECMO) are generally considered as the fi rst choice in MCS for fulminant myocarditis in Japan. 4 Although VAB is economical and therefore readily available, it is associated with problems such as ischemic complications in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate associated with fulminant myocarditis has been increasing with advances in various systems of MCS. 3 Methods of VAB such as percutaneous cardiopulmonary support (PCPS) or extracorporeal membrane oxygenation (ECMO) are generally considered as the fi rst choice in MCS for fulminant myocarditis in Japan. 4 Although VAB is economical and therefore readily available, it is associated with problems such as ischemic complications in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Other BTT trials have also reported a high incidence of infection (72). In the ISHLT database, the incidence of postoperative infection was 32.5% (41).…”
Section: Complicationsmentioning
confidence: 92%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited. 50% of the time; however, this rate decreases as the experience with device implantation grows (16,17). About 50% of patients require reoperation for bleeding, while death due to bleeding was reported to be in the range of 0 to 15% (17,18).…”
Section: Complications With Vadsmentioning
confidence: 99%
“…50% of the time; however, this rate decreases as the experience with device implantation grows (16,17). About 50% of patients require reoperation for bleeding, while death due to bleeding was reported to be in the range of 0 to 15% (17,18). Infection is another serious complication and the primary cause of death in long-term LVAD patients.…”
Section: Complications With Vadsmentioning
confidence: 99%